Exploratory Action Research in Language Teacher Education: Opportunities and Challenges - Dilafruz Sarimsakova (Jurnal Teknologi Pendidikan, 2025)
This article explores the role of Exploratory Action Research (EAR) in language teacher education, focusing on both its potential and the barriers to its effective implementation. EAR offers student teachers an opportunity to engage in classroom-based inquiry, enhancing their professional development through reflective teaching and systematic research. Drawing from theoretical frameworks and practical applications, this article discusses how EAR strengthens inquiry skills, connects theory with practice, fosters collaboration, and supports context-sensitive teaching. It also outlines the main challenges such as time constraints, limited research experience, and institutional barriers. Recommendations are provided for successfully integrating EAR into teacher education programs